Influence of differential heat treatment on foodstuffs with apples received by the convection-thermoradiation method of drying - Strelchenko, Ljudmila; Dubkovetskyy, Igor; Malezhik, Ivan (My University, 2019)
The influence of differential heat treatment on products from apples with different sugar content in semi-finished products is considered.
Keywords: apple; snack; candied fruits; blanching; drying; яблуко; снек; цукат; бланшування; сушіння; кафедра процесів і апаратів харчових виробництв